GLP-1 receptor agonists have a sustained stimulatory effect on corticosterone release after chronic treatment. Issue 1 (3rd December 2014) - Krass, Maarja; Volke, Annika; Rünkorg, Kertu; Wegener, Gregers; Lund, Sten; Abildgaard, Anders; Vasar, Eero; Volke, Vallo
Abstract : Objective: Glucagon-like peptide 1 (GLP-1) receptor agonists are a new group of antidiabetic medications quickly gaining popularity. We aimed to examine behavioural and neuroendocrine changes following chronic treatment with GLP-1 receptor agonists in animal models. Methods: The effects of chronic treatment with GLP-1 receptor agonists were determined on behavioural parameters [anxiety level in the light–dark compartment test, the motor activity in automated activity cages, immobility in the forced swimming test (FST)] and on corticosterone release in mice. The possible antidepressant effect of chronic liraglutide treatment was also studied in Flinders Sensitive Line (FSL) rats, a genetic model of depression. Results: Two weeks of treatment with exenatide (10 µg /kg twice daily) or liraglutide (1200 µg/kg once daily) did not affect the anxiety level in a light–dark compartment test nor induce an antidepressant-like effect in the FST in mice. Moreover, chronic treatment with liraglutide had no effect on depression-related behaviour in FSL rats. Interestingly, hypolocomotion induced by the drugs in mice disappeared after chronic dosing. Both of the GLP-1 receptor agonists induced robust increases in corticosterone levels in mice under basal conditions as well as in the case of combination with swimming stress. Remarkably, exenatide was as potent a stimulator of corticosterone release after 2 weeks as after acute administration. Conclusions: The increases in corticosterone release seen after acute exenatide or liraglutide treatment do not abate after 2 weeks of treatment demonstrating that tolerance does not develop towards this particular effect of GLP-1 agonists.